Antropologi Sosial Perkembangan Tradisi, Adat dan Seni Islam di Nusantara: Jawa, Sunda dan Melayu - Ali, Nur; Nur, Putri (SiNORA, 2025)
This study aims to analyze the development of Islamic traditions, customs, and arts in the archipelago, with a focus on the Javanese, Sundanese, and Malay regions. Using qualitative research with a library research approach, this study examines the interaction between local culture and Islamic teachings, and how the acculturation between the two creates a unique wealth of traditions in each region. This study highlights the role of art, traditional ceremonies, and architecture in the spread of Islam, as well as the contribution of scholars and sunans in using local culture as a medium for moderate and harmonious da'wah. The results of this study are expected to provide a deeper understanding of the dynamics of Islamic culture in the archipelago and its role in forming a sustainable cultural identity.